MODEL EVAKUASI KERAMAIAN DALAM GEDUNG MEMILIKI BEBERAPA PINTU KELUAR DENGAN MEMPERHATIKAN KEPANIKAN INDIVIDU - Ghaitsa Deiwa Karufa; Defri Ahmad (Jurnal Lebesgue : Jurnal Ilmiah Pendidikan Matematika, Matematika dan Statistika, 2023)
The purpose of this study is to determine the effect of panic on evacuation time. Evacuation is the movement of individuals from a place in danger to a safer place. Evacuation is usually done when there is an emergency such as an earthquake, fire or attack, which will make the movement of individuals difficult. Individuals who are in an emergency will feel panic. The panic that occurs will cause individuals to lose their way to a safer place such as an exit. This research is a basic or theoretical research. The evacuation model uses cellular automata that simulates the behavior of individuals in cells for the evacuation process. This model considers the panic factor in the evacuation process which will affect the steps taken by individuals. Individual steps based on transition probabilities will obtain evacuation time. The parameters used are static coefficient, dynamic coefficient, and panic coefficient. Simulation using software by entering the grid size, obstacle position, exit position, individual position and parameters. Based on the simulation results, it is obtained that the increase in individual panic, the longer the evacuation time